Effectiveness of Mycophenolate Mofetil in the Treatment of Pediatric Anti-NMDAR Encephalitis: A Retrospective Analysis of 6 Cases - Hao, Xiao-sheng; Wang, Jiang-tao; Chen, Chen; Hao, Yun-peng; Liang, Jian-min; Liu, Song-yan (Frontiers in Neurology, 2020)
Objective: To explore the effectiveness and safety of mycophenolate mofetil (MMF) as a second-line medication in the treatment of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, the most common and severe autoimmune encephalitis. Methods: The clinical data of six children with anti-NMDAR encephalitis admitted to the First Hospital of Jilin University were retrospectively analyzed, and the effectiveness and safety of MMF were evaluated. Results: Six children with anti-NMDAR encephalitis were treated with MMF in the 2nd or 3rd treatment disease event (3 cases vs 3 cases). MMF initiation was mean 19.2 months (range 6-39 months) after disease onset at a mean dose of 25.6 mg/ kg (range 19.6-28.4 mg/kg) for 14 months (range 6-26 months). Only two patients had transient mild diarrhea within 2 weeks of MMF application. During follow-up, one patient relapsed whilst on MMF, one patient discontinued MMF, and 4 cases were still on MMF. Conclusion: The use of MMF in anti-NMDAR encephalitis may be effective and safe. MMF can be used as one of the relapse prevention options in patients who already have relapsed or possibly even after the first event. Delayed use may be the main reason for MMF failure.